Macerals Analysis Seam M2 Muaraenim Formation, : Implication Toward Coal Facies and Coal Rank in Kendi Hill, South Sumatra - Yonathan Mangatur Rajagukguk; Stevanus Nalendra Jati (Journal of Geoscience, Engineering, Environment, and Technology, 2018)
The Muaraenim Formation is a coal bearing formation in South Sumatra Basin of the Late Miocene – Pliocene. Shell (1978) divides this formation based on coal seam content are: M1, M2, M3, and M4. Coal seam in this area include in seam M2 member, with the general characteristics of the presence of silicified coal on the roof and floor of coal seams as a marker. The administration of the research area is located in east Kendi Hill, South Sumatra. The Kendi Hill is composed of adesite igneous rocks that intruded Muaraenim Formation in unconformity at the time of Pleistocene. This study aims to determine the environment of coal depositional based on maceral analysis and determine the factors influence the physical characteristics of coal seams in Kendi Hill. Data that has been obtained from the field, then conducted a selection process. The number of samples analyzed were nine sample based on near and far to the Kendi Hill spread from the southern, central, and northern of the location. The result of the analysis will display the maceral diagram. Megascopically, coal seam in the Kendi Hill are black, dull with bright, uneven – subchoncoidal, blackish brown in streak, have a pyrite and resin. The thickness of the coal seams ranges from 0,45 to 14 meters. Based on the maceral analysis, the coal seam in the Muaraenim Formation is composed dominated by vitrinite, then liptinite, inertinite and mineral matter pyrite (1,6-6,6%). Vitrinite reflectance of coal in the research area ranges from (0,37-0,48%) that included to the Sub bituminous – High Volatile Bituminous C. From the results of Tissue Preservation Index and Gelification Index value indicated that the environment of coal depositional in the research area was a limnic to wet forest swamp. Whereas the deposition of the Muaraenim Formation in deltaic environment (Transitional lower delta plain).